Effects of Different Organic Materials on the Yield and Some Quality Specifications of Fruits in Tomato. - Ece, Ali; Uysal, Fatma (Asian Journal of Chemistry, 2010)
The aim of this study is to investigate the effect of green fertilization and applications of vatious organic materials on quality of tomatoes. Common vetch (Vici sativa L.) was used as green fertilization plant. Organic material used in the study included sheep manure, molasses and Org-E-Vit. Yield (g/plant), total soluble solid (%), ascorbic acid (mg 100 g-1) and pH were measured. In tomato, green fertilization significantly affected total water-soluble dry matter while green fertilization x applications interactions highly significantly affected ascorbic acid content. Applications investigated in this study did not significantly affect other characteristics. It was observed that green fertilization plants and organic materials used in organic farming have effects on some fruit quality chatacteristics.